Emergence of traveling waves in linear arrays of electromechanical oscillators. Issue 1 (December 2018) - Dou, Yong; Pandey, Shashank; Cartier, Charles; Miller, Olivia; Bishop, Kyle
Abstract Traveling waves of mechanical actuation provide a versatile strategy for locomotion and transport in both natural and engineered systems across many scales. These rhythmic motor patterns are often orchestrated by systems of coupled oscillators such as beating cilia or firing neurons. Here, we show that similar motions can be realized within linear arrays of conductive particles that oscillate between biased electrodes through cycles of contact charging and electrostatic actuation. The repulsive interactions among the particles along with spatial gradients in their natural frequencies lead to phase-locked states characterized by gradients in the oscillation phase. The frequency and wavelength of these traveling waves can be specified independently by varying the applied voltage and the electrode separation. We demonstrate how traveling wave synchronization can enable the directed transport of material cargo. Our results suggest that simple energy inputs can coordinate complex motions with opportunities for soft robotics and colloidal machines. For small scale biological systems such as cilia, movement is achieved by rhythmic motor patterns that organize spontaneously within arrays of driven oscillators. The authors show that conductive spheres oscillating between biased electrodes create similar traveling wave motions which can be used to direct the transport of cargo.